Short-term changes of anxiety in adolescent female athletes - Young, J. A.; Quatman-Yates, C. C.; Mohr, D.; Butz, C.; Allison, K. E.; Onate, J. A.; Valasek, A. E. (International Journal of Athletic Therapy & Training, 2025)
Anxiety is common in adolescents but short-term changes in anxiety have not been studied. The purpose of this observational study was to describe how anxiety changes in high school female athletes over 16 weeks. Participants completed the Generalized Anxiety Disorder-7 (GAD-7) every other week. We categorized participants as elevated if their GAD-7 score was >9 and a score change of =4 classified those with clinically meaningful anxiety change. Of the 28 participants, 30% reported elevated GAD-7 scores at least once and 80% reported anxiety changes =4. Athletic trainers are poised to monitor anxiety and can promote optimal mental health by referring those with elevated GAD-7 scores for timely intervention.